2000
DOI: 10.1063/1.480993
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of laser cooling of room temperature trans-stilbene upon excitation to the S1 state

Abstract: Femtosecond Raman spectra of cis-stilbene and trans-stilbene with isotopomers in solution J. Chem. Phys. 137, 244505 (2012); 10.1063/1.4769971Franck-Condon analysis of laser-induced fluorescence excitation spectrum of anthranilic acid: Evaluation of geometry change upon S 0 → S 1 excitation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…12 The rate was found to be minimal at the 0 0 0 transition frequency and substantially rising both to a͒ the red and to the blue of the 0 0 0 frequency. 12 The rate was found to be minimal at the 0 0 0 transition frequency and substantially rising both to a͒ the red and to the blue of the 0 0 0 frequency.…”
Section: Introductionmentioning
confidence: 88%
“…12 The rate was found to be minimal at the 0 0 0 transition frequency and substantially rising both to a͒ the red and to the blue of the 0 0 0 frequency. 12 The rate was found to be minimal at the 0 0 0 transition frequency and substantially rising both to a͒ the red and to the blue of the 0 0 0 frequency.…”
Section: Introductionmentioning
confidence: 88%
“…In recent years evidence for cooling in trans-stilbene has been found by Warmuth et al, 36 who observed a dependence of the isomerization rate on the laser excitation frequency in bulb experiments. Just such an effect would be expected on the basis of the cooling mechanism.…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, spectroscopic evidence for cooling at pressures around 1 atm has been recently reported. 36 Following Gershinsky and Pollak, 19 we can approximately estimate the possible effects of cooling on the isomerization rate by calculating the excess vibrational energy of the molecule Figure 10. Direct comparison of LRMT and experimental isomerization rates for trans-stilbene isotopomers.…”
Section: Thermal Isomerization Ratementioning
confidence: 99%
“…5,10,[18][19][20][21] Hamaguchi proposed a "dynamic polarization model" in which the time evolution is dominated by the stochastic polarization of the mode, induced by the solvent. 18 Kovalenko et al 3 suggested that the change in the dynamics, from broadening of the FWHM at low excitation energies to narrowing at high excitation energies serves as an indication of the initial temperature of the excited mode.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of this relaxation depends upon many factors such as solute-solvent coupling, intramolecular-vibrationalrelaxation, temperature of the bath and the initial state of the molecule. [1][2][3][4][5][6][7][8][9][10] Many experiments have been carried out to probe the time-dependent vibrational relaxation of the Stilbene molecule. [3][4][5][6][7][8][9][11][12][13][14][15][16][17] The measured data on a given vibrational band are characteristically summarized in terms of the time evolution of the instantaneous maximum of the band and its full width at half maximum (FWHM).…”
Section: Introductionmentioning
confidence: 99%